Problematika dan Perkembangan Perbankan Syariah di Indonesia dalam Era Globalisasi - Wiwi Widia Argita; Neneng Fitriah; Abu Bakar Sidiq; Rasidah Novita Sari (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This research aims to analyze the problems and development of sharia banking in Indonesia in the context of globalization. Sharia banking in Indonesia has experienced significant development during the era of globalization. Globalization is a process of international integration that occurs due to the exchange of world views, products, thoughts and other cultural aspects. The progress of transportation and telecommunications infrastructure, including the emergence of the telegraph and the Internet, is a major factor in globalization which increasingly encourages interdependence of economic and cultural activities. The era of globalization has brought changes to the world economic order and presented challenges and opportunities for sharia banking. However, with the development of sharia banking, various problems and challenges have arisen that need to be overcome, the central problem is the lack of socialization and education to the community, as well as competition with conventional institutions which is also a challenge for sharia banking in Indonesia. The analysis method used by the author is a qualitative approach. The results of the research in this journal are the innovation of Islamic banking products, developing digital banking and increasing human resources as a strategy for the development of Islamic banking in Indonesia in the era of globalisation.